Relevansi Nilai Earnings dengan Pendekatan Terintegrasi: Hubungan Nonlinier - Rahmawati Rahmawati (Jurnal Akuntansi dan Auditing Indonesia, 2005)
The purpose of this research is to identify nonlinear relationship between earnings and stock return. This research provides an empirical examination of value relevance of earnings used by investors in decision making, stressing on return model. This research uses 41 manufactur¬ing firms listed in Jakarta Stock Exchanges, which are selected by using purposive sampling method. Those selected firms announced their financial statement during 1998 until 2002. The hypo¬thesis is tested by NLS (Non Linear Least Square) regression model. The research shows that regression coefficients of earnings are not significants before, when, and after the announcement of financial statements, so that H1 is reject¬ed or there is no nonlinear relationship between earnings and stock return, except in 2000 (V17), the regression coefficient of earnings is significant, so that H1 is ac¬cepted or there is nonlinear re¬lationship between earnings and stock return. R2 (R-squared) along the observation period (1999-2002) has changed. The results indicate that value relevance of earnings has changed year to year.Based on the result of the research, it can be concluded that earnings information begin to lose their value relevance, so the investor is suggested to use another information, such as cash flow information in decision making of investment.Keywords: earnings, stock return, non-linear, value relevance